Development of Automated BIM Data Quality Pre-Check (BDQPC) System in Architectural Design Phase - Choi, Jungsik; Kim, Inhan; Shin, Jihye (International Journal of Engineering and Technology, 2019)
Recently, the mandates on utilizing Building Information Modeling (BIM) implemented by the public institutions of many countries have had a great impact on the significantly increasing practices of BIM. BIM is a technology that supports a process of information exchange and communication by integrating, interchanging, and reusing data during the building lifecycle. The improvement of work efficiency and productivity that comes with BIM adoption depends on the consistency and accuracy of data. To maximize the benefit of BIM, interest in BIM data quality has been increasing all over the world. The delivery of BIM data is mandatory in advanced countries, and these countries are promoting automated BIM quality checking. The BIM data quality pre-check (BDQPC), which is conducted by a designer in the design phase, offers opportunities for quality improvement by continuously assessing BIM data. However, the BIM quality pre-check is being conducted under the arbitrary interpretation of users because of the absence of specific review factors and assessment methods for checking BIM quality. The purpose of this study is to suggest an automated BIM quality pre-checking system to improve BIM design quality effectively and efficiently. It is expected to meet the ownerâ€™s requirements and to minimize the additional cost and time incurred from revising and reproducing data by ensuring its consistency and accuracy.Â Â